Land, Water, Air and Freedom The Making of World Movements for Environmental Justice - Martínez-Alier, Joan (Edward Elgar Publishing, 2023)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This ground-breaking book makes visible the global counter-movement for environmental justice, combining ecological economics and political ecology. Using 500 in-depth empirical analyses from the Atlas of Environmental Justice, Martínez-Alier analyses the commonalities shared by environmental defenders and offenders respectively.